Dwelling overheating in risk in cool climates: Assessing the risk in the context of retrofit and climate change in Ireland - M. Mulville; S. Harrington; C. Li; K. Raushan; E. Essien-Thompson; C. Ahern (Indoor Environments)
In the context of large-scale retrofit and the predicted impacts of climate change, overheating risk in dwellings in cool climates is an increasing cause for concern. This review-based paper, supported by Dynamic Simulation Modelling, explores the magnitude of overheating risk in dwellings in a cool climate, identifying and quantifying dwelling typologies most at risk. Key contributory factors to overheating, including typology and characteristics, specification and design (including the role of retrofit), internal factors and occupant activities and external conditions are reviewed and existing regulatory frameworks assessed, to highlight potential limitations. Building upon this, the paper makes the case for the use of robust Dynamic Simulation Modelling supported by localised weather files accounting for the Urban Heat Island effect and occupant behaviour. In addition, the paper, for the first time, reviews the future building simulation weather files from Ireland’s National Meteorological service highlighting the potential impact of climate change on overheating projections. The files predict increased ambient temperatures and solar radiation along with a shift in the peak design month (from July to August), with reductions in mean wind speeds over time. Unlike other climate locations, the diurnal temperature swing into the future is not predicted to reduce, supporting the use of thermal mass to mitigate overheating. Middle, top-floor apartments and compact dwellings are at increased overheating risk as are more modern (thermally) or deep retrofitted dwellings. For Ireland, up to 10 % of the existing occupied stock may be at risk of overheating, potentially impacting upon 519,200 individuals. This percentage is likely to increase over time. The findings have implications for housing in cool climates where large investments are being made in national retrofit strategies that could exacerbate the problem if not considered alongside overheating mitigation strategies.